'The deadliest thing that keeps the seas': the technology, tactics and terror of the submarine in The War Illustrated magazine. (2nd January 2017) - Rayner, Jonathan
ABSTRACT: This paper explores the representation of the submarine as an embryonic and influential factor in the First World War. In War Illustrated, reporting of German and British submarines assumed a high profile because of spectacular successes (such as U-9's sinking of HMS Aboukir, Cressy and Hogue), and because of the perceived inactivity of the opposing battle fleets. The evolution of the magazine's reporting of the submarine (from dismissal of its danger, to condemnation of its 'piratical' deployment, to celebration of its technological advancement) reflected the divisive characteristics of submarine warfare and the troubled reputation of the Royal Navy in the public imagination. The submarine's emergence within twentieth-century warfare can be traced through the problematic popular responses to its unique capabilities and contribution to the naval campaign.